SUPERVISI MANAJERIAL PENGAWAS MADRASAH ALIYAH - Yosa Meriza (Manajer Pendididikan, 2015)
The purpose of this research was to describe clearly the managerial supervision conducted by the superintendent of madrasah aliyah in MA Al Muhajirin Tugumulyo Musi Rawasdistrict. This research used descriptive qualitative approach. The subject of this research was superintendents, headmaster, deputy head of curriculum, deputy head of student, and the head of the administrative staff. The result of the study concluded as follow: (1) the planning include perspective, mission, purpose, program, target, and schedule, (2) the implementation same with planning, (3) the monitoring and evaluation include monitor, evaluation, reporting, anddocumentation, (4) in terms of the follow-up are founding and next new program of supervision.Keyword: managerial supervision, Madrasah Aliyah, superintendent